Supramolecular hydrogen bonding interactions of novel 1,3,5-benzenetricarbonyl trisubstituted alkyl for anion sensor applications - Matmin, Juan (Trans Tech Publication, 2014)
Herein we report the first example of benzene-1,3,5-tricarboxamide bearing hydrophobic aminododecane side chains (1) which spontaneously forms supramolecular network by a hydrogen bonding interaction. The compound 1 was synthesized by Schotten-Baumann reaction of 1,3,5-benzenetricarbonyl trichloride and 1-aminododecane in the presence of N,N-diisopropylethylamine. Nuclear Magnetic Resonance (NMR), Mass Spectrometry (MS), and Fourier Transform Infrared (FTIR) spectroscopies have proved the successful synthesis of 1 in 93% as white powder solid. The supramolecular organization was successfully utilized for sensing of nitrate anions by deformation of the hydrogen bonding to form inactive nitroso groups.